Food waste: Evidence from a university dining hall in Brazil - Lucas Rodrigues Deliberador; Mário Otávio Batalha; Michelle Chung; Aldara Da Silva Cesar (RAE: Revista de Administração de Empresas, 2021)
Studying the causes of food waste and potential interventions for minimizing it is one of the main concerns of those who work with food on all levels. Food in the education sector, which includes dining halls in higher education institutions, is among the sectors that deserve attention, since its consumers generate significant amounts of food waste. There is still a lack of studies, however, addressing the problem of food waste in dining halls. The general objective of this study is to investigate food waste in a Brazilian university dining hall, and consumer perceptions of the meals. By means of a questionnaire, it was possible to investigate the main perceptions of consumers, and what might be behind the waste generated. Spearman’s correlation was performed in order to verify the correlation between consumer food waste and consumer perceptions as to the reasons behind the food waste that is generated. It was found that average waste was 68g/consumer. It was also observed that consumers who placed their food in trays wasted more food than those who chose to eat from a dish. All the collected information was used to propose potential interventions to reduce food waste in university dining halls.